Perancangan Jaringan Fiber To The Home Berbasis Gigabit Passive Optical Network Dengan Dual Stage Passive Splitter - Arya Tri Andhika, I Gusti Ngurah; Sukadarmika, Gede; Indra ER, Ngurah (Majalah Ilmiah Teknologi Elektro; Vol 22 No 1 (2023): (Januari - Juni) Majalah Ilmiah Teknologi Elektro, 2023)
Abstract — This study was conducted to find out which network is more effective and the quality of the existing network, Design A, and Design B at Wongaya Cluster. Existing network has 368 homepass, with 259 homeconnected users. Using the Farthest FAT (F.8) output attenuation of field measurement was -20.11 dBm, the optisystem test obtain an output attenuation -19.954 dBm, and based on power link budget calculation, output attenuation was -20.399 dBm. Existing network has a projection for the next five years of 462 users. Design A has 496 homepasses and tested on farthest FAT (G.4) testing on the optisystem to obtain an output attenuation of -19.704 dBm, and based on the calculation of the power link budget, an output attenuation of -20.7414 dBm was obtained. Design B has 256 homepasses and tested on the furthest FAT (H.4) testing on the optisystem to obtain an output attenuation of -16.765 dBm, and based on calculation of the power link budget, output attenuation was -17.09175 dBm. Based on results of this test, Design A is more effective design to use because it can meet customer needs in five years with quality according to ITU-T and Company standards. Keywords— FTTH, GPON, attenuation, homepass, homeconnected, link power budget